Sequential complex bilateral total hip arthroplasty in neglected acetabular fractures – A case report. Issue 1 (February 2022) - Jha, Aaradhana J.; Jacob, Roshan; Sowers, Mackenzie; Alexander, Bradley; Shah, Ashish; Naranje, Sameer
الملخص: تتعقد العديد من حالات كسور الحُق بسبب الإهمال، مما يؤدي إلى مزيد من الضرر لرأس عظم الفخذ بما في ذلك الفصال العظمي بعد الصدمة والتصلب. تؤدي هذه الأحداث الضائرة في النهاية إلى تعقيدات في معالجة هؤلاء المرضى. ويعتبر رأب مفصل الورك الكلي خيارا جراحيا لتحسين ثبات المفصل ووظيفته، بالإضافة إلى التحكم في الألم. أبلغنا عن ذكر يبلغ من العمر ٧٠ عاما مصابا بكسر حُقِّي ثنائي مهمل، قدم إلينا مع الفصال العظمي بعد الصدمة والتصلب والنتوء. على الرغم من الفارق الكبير بين طول الطرفين السفليين مع تشوه الورك الأيسر، فقد خضع المريض لرأب مفصل الورك الكلي الأيمن وتعافى بثبات ملحوظ. وبعد عام واحد، خضع المريض بنجاح لرأب مفصل الورك الكلي الآخر. الآن بعد مرور عام على العلاج الجراحي، أصبح المريض بدون ألم مع قدرة ملحوظة على الحركة. عند علاج مريض مصاب بكسر حقي مهمل وفصال عظمي بعد الصدمة ثنائي فإن رأب مفصل الورك الكلي الثنائي هو خيار علاجي قابل للتطبيق مع نتائج مواتية للمريض. Abstract: Severe cases of acetabular fractures are complicated, leading to further damage to the femoral head and post-traumatic osteoarthritis (PTOA). These adverse events eventually lead to complexities in the management of patients with the aforementioned conditions. Total hip arthroplasty (THA) is a surgical option for improving both stability and functionality, and for controlling pain in patients with PTOA. Herein, we report the case of a 70-year-old male patient with neglected bilateral acetabular fracture who presented with PTOA and protrusion. Despite significant limb-length discrepancy with the deformity of both hips, the patient underwent a successful right THA and recovered with remarkable stability. One year later, the patient underwent successful left THA. One year following the surgical treatment, the patient is pain free with notable mobility. When treating a patient with a neglected acetabular fracture and bilateral PTOA, bilateral THA is a viable treatment option with favourable patient outcome.